2013
DOI: 10.1001/jama.2013.167
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Promoting Longer-term and Exclusive Breastfeeding on Adiposity and Insulin-like Growth Factor-I at Age 11.5 Years

Abstract: Importance Evidence that longer-term and exclusive breastfeeding reduces child obesity risk is based on observational studies that are prone to confounding.Objective To investigate effects of an intervention to promote increased duration and exclusivity of breastfeeding on child adiposity and circulating insulin-like growth factor (IGF)-I, which regulates growth.Design, Setting, and Participants Cluster-randomized controlled trial in 31 Belarusian maternity hospitals and their affiliated clinics, randomized in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
152
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 155 publications
(162 citation statements)
references
References 46 publications
6
152
1
3
Order By: Relevance
“…The latent effects of breastfeeding may explain the inconsistency in previous results on the association between BMI and breastfeeding (13,23,24). In previous studies, the children's ages ranged predominantly from 3 to 6 years (7,(24)(25)(26) or the children were over 9 years old (6,12). In our study, a significant slower increase of BMI with age was observed in both boys and girls in late childhood, that is, after 7 years in boys and at 8 years in girls, who were breastfed compared with those who were formula-fed.…”
Section: Discussionmentioning
confidence: 98%
“…The latent effects of breastfeeding may explain the inconsistency in previous results on the association between BMI and breastfeeding (13,23,24). In previous studies, the children's ages ranged predominantly from 3 to 6 years (7,(24)(25)(26) or the children were over 9 years old (6,12). In our study, a significant slower increase of BMI with age was observed in both boys and girls in late childhood, that is, after 7 years in boys and at 8 years in girls, who were breastfed compared with those who were formula-fed.…”
Section: Discussionmentioning
confidence: 98%
“…15,16 However, research on breastfeeding and overweight has demonstrated mixed results. 17,18 A World Health Organization review in 2007 supported the link, 18 whereas others [19][20][21] found no association between duration of breastfeeding and adulthood overweight. Research findings are also mixed on the outcomes of early or late introduction of complementary foods.…”
Section: Infant-specific Food Parenting Behaviorsmentioning
confidence: 99%
“…De nombreuses études se sont par la suite intéressées aux relations entre le mode d'allaitement et le risque d'obésité à long terme, et concluaient, en général, à un effet protecteur faible de l'allaitement maternel [30] avec des résultats parfois contradictoires [31]. Le seul essai randomisé permettant d'évaluer les effets à long terme de la promotion de l'allaitement maternel en maternité, n'a pas montré d'effet sur le risque de surpoids de l'enfant lorsqu'il atteint ses 11 ans [32]. Outre des facteurs de confusion qui n'ont pas toujours pu être pris en compte de façon similaire dans les différentes études, les caractéristiques de l'alimentation des enfants non allaités par leur mère, qui servent de comparateur dans les études observationnelles, participent à la variabilité des résultats de ces travaux.…”
Section: Les Enjeux Liés Aux Modifications Du Statut Nutritionnel Matunclassified